Mechanisms For Developing Professional Competence Through The Use Of Digital Resources In Music Pedagogy (Open Academia: Journal of Scholarly Research, 2026)
This article explores the mechanisms for developing professional competence in music pedagogy through the effective use of digital resources. In the context of rapid digitalization of education, the integration of modern technologies into the teaching process has become a key factor in improving the quality of music education. The study analyzes the pedagogical potential of digital tools, including multimedia platforms, interactive applications, online learning environments, and virtual instruments, in enhancing the professional skills of future music teachers. Special attention is paid to the formation of methodological, technological, and creative competencies through digital means. The article identifies key mechanisms such as digital content integration, interactive teaching strategies, independent learning support, and continuous professional development via online resources. Furthermore, the role of digital literacy in shaping innovative teaching approaches and increasing student engagement is highlighted.